Symptoms of depression and quality of life in functional dyspepsia patients - Agus Siswanto, Muhammad Eko Cahyanto Neneng Ratnasari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Dyspepsia is a common disorder characterized by heartburn, nausea, vomiting, bloating, feelingof fullness or early satiety, and belching. Functional dyspepsia (FD) or non-ulcer dyspepsia is asyndrome without any physical or endoscopic abnormalities underlying these symptoms. Theimpacts of FD on psychological disturbances and quality of life in patients have been postulated.However, it has not much been a concern. This study was conducted to evaluate the relationshipbetween symptoms of depression and quality of life in patients with FD. This was an observationalstudy with cross-sectional design involving 30 patients. The symptoms of depression weremeasured by beck depression inventory (BDI) and the quality of life of patients were measuredby SF-36. The results showed that FD were more suffered consecutively by female patients(66.7%), age over 45 years (53.4%), housewives (56.6%), educated graduates (56.6%) andmarried (90.0%). Moreover, patients who experienced symptoms of clinical depression withlow, moderate and severe levels were 16.3%, 33.3% dan 10.0%, respectively. A significantcorrelation between depressive symptoms and the overall of patients quality of life was observed(r = 0.481; p<0.05). Furthermore analysis showed that among eight domains of health in SF-36analyzed, a negative significant correlation was observed between the depressive symptoms andthe three domains of health i.e. general physical function, limitation of motion caused byphysical problems, and vitality. In conclusion, there is a negative correlation between depressivesymptoms and quality of life in patients with FD.